DEPDC5 protects CD8+ T cells from ferroptosis by limiting mTORC1-mediated purine catabolism - Song Li; Xinxing Ouyang; Hongxiang Sun; Jingsi Jin; Yao Chen; Liang Li; Qijun Wang; Yingzhong He; Jiwen Wang; Tong‐Xin Chen; Qing Zhong; Yinming Liang; et al. (2024)
Abstract Peripheral CD8 + T cell number is tightly controlled but the precise molecular mechanism regulating this process is still not fully understood. In this study, we found that epilepsy patients with loss of function mutation of DEPDC5 had reduced peripheral CD8 + T cells, and DEPDC5 expression positively correlated with tumor-infiltrating CD8 + T cells as well as overall cancer patient survival, indicating that DEPDC5 may control peripheral CD8 + T cell homeostasis. Significantly, mice with T cell-specific Depdc5 deletion also had reduced peripheral CD8 + T cells and impaired anti-tumor immunity. Mechanistically, Depdc5 -deficient CD8 + T cells produced high levels of xanthine oxidase and lipid ROS due to hyper-mTORC1-induced expression of ATF4, leading to spontaneous ferroptosis. Together, our study links DEPDC5 - mediated mTORC1 signaling with CD8 + T cell protection from ferroptosis, thereby revealing a novel strategy for enhancing anti-tumor immunity via suppression of ferroptosis.